Effectiveness of an Educational Program on Childhood Tuberculosis Supported on Information and Communication Technologies Aimed at Community Mothers from Cartagena - Castillo Avila, Irma Yolanda; Hernández Escolar, Jacqueline; Alvis Estrada, Luis Reinaldo (Investigación y Educación en Enfermería, 2016)
Objective. To evaluate the effectiveness of an educational program using ICT to improve knowledge on childhood tuberculosis, in Family Women and Childhood (FAMI, for the term in Spanish) of Cartagena (Colombia). Methods. A controlled and randomize prevention trial without blinding was conducted on a sample of 50 community mothers from a location in Cartagena. The educational program combined five face meetings and support from information and communication technologies (ICT). With the control group only five education sessions were developed. Results. The average number of users in charge per community mother corresponds to 11 and the average number of children in charge was eight. Although in both groups the total score from the pre-test to the post-test was improved (Intervention = 29.9 to 38.2, and Control = 31.9 to 36.8), this difference in the total and by modules was higher in the intervention group. Module 5 of Activities to identify suspected cases, monitor children, and care routes obtained in both groups the biggest difference in score between the pre- and post-test moments. Conclusion. The education strategy that involved the virtual information component resulted significantly more effective to improve knowledge than the traditional education strategy. How to cite this article: Castillo IY, Hernández J, Alvis LR. Effectiveness of an Educational Program on Childhood Tuberculosis Supported on Information and Communication Technologies Aimed at Community Mothers from Cartagena. Invest. Educ. Enferm. 2016; 34(3): 465-473